Possible roles of exercise and apelin against pregnancy complications - Alizadeh Pahlavani, Hamed (Frontiers in Endocrinology, 2022)
Abstract The prevalence of maternal obesity during pregnancy is associated with the risk of gestational diabetes, preeclampsia, and cardiomyopathy. Environmental factors such as active lifestyles and apelin may lead to beneficial changes. In rats, apelin and exercise (45 to 65% VO2max for 6 to 9 weeks) during pregnancy increase brown adipose tissue (BAT) proteins such as Cidea, Elovl3, UCP1, PRDM16, and PGC-1α in males and females fetuses, while white adipose tissue (WAT) is reduced. In humans and animals, apelin and exercise stimulate the expression of the glucose transporters (GLUT1/2/4) in the muscle and adipose tissue through the PI3K/Akt and AMPK pathways. Hence, exercise and apelin may are known as regulators of energy metabolism and be anti-obesity and anti-diabetic properties. In mice, exercise also creates a short-term hypoxic environment in the pregnant mother, activating HIF-1, VEGF, and VEGFR, and increasing angiogenesis. Exercise and apelin also increase vasodilation, angiogenesis, and suppression of inflammation through the L-arginine/eNOS/NO pathway in humans. Exercise can stimulate the ACE2-Ang-(1-7)-Mas axis in parallel with inhibiting the ACE-Ang II-AT1 pathway. Exercise and apelin seem to prevent preeclampsia through these processes. In rats, moderate-intensity exercise (60 to 70% VO2max for 8 weeks) and apelin/APJ also may prevent pathological hypertrophy in pregnancy by activating the PI3K/Akt/mTOR/p70S6K pathway, PI3k-Akt-ERK1/2-p70S6K pathway, and the anti-inflammatory cytokine IL-10. Since pre-clinical studies have been more on animal models, future research with scientific guidelines should pay more attention to human specimens. In future research, time factors such as the first, second, and third trimesters of pregnancy and the intensity and duration of exercise are important variables that should be considered to determine the optimal intensity and duration of exercise.